2018
DOI: 10.3389/fphys.2018.01055
|View full text |Cite
|
Sign up to set email alerts
|

Permeation and Rectification in Canonical Transient Receptor Potential-6 (TRPC6) Channels

Abstract: Transient receptor potential-6 channels are widely expressed cation channels that play a role in regulating Ca2+ dynamics, especially during G protein-coupled receptor signaling. The permeation of cations through TRPC6 is complex and the relative permeability to Ca2+ relative to monovalent cations appears to be highly voltage-dependent and is reduced upon membrane depolarization. Many investigators have observed complex current-voltage (I-V) relationships in recordings of TRPC6 channels, which often manifest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…We previously reported that TRPC6 channels contribute to LPSinduced inflammatory response in human bronchial epithelial cells, which implies that TRPC6 may be a therapeutic target in bronchial epithelial inflammation 36 . It has been well described in many cell types and tissues that the activity of TRPC6 channel is redox-sensitive, while it seems to have different phenotype according to different cell types 23,37 . In podocytes, HEK 293T cells and vascular myocytes, ROS not only activates TRPC6 already in the plasma membrane but also upregulates the expression of TRPC6 in the surface [38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that TRPC6 channels contribute to LPSinduced inflammatory response in human bronchial epithelial cells, which implies that TRPC6 may be a therapeutic target in bronchial epithelial inflammation 36 . It has been well described in many cell types and tissues that the activity of TRPC6 channel is redox-sensitive, while it seems to have different phenotype according to different cell types 23,37 . In podocytes, HEK 293T cells and vascular myocytes, ROS not only activates TRPC6 already in the plasma membrane but also upregulates the expression of TRPC6 in the surface [38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the stable over-expression of TRPC6 in HEK-293 cells causes an intracellular Zn overload, a feature not found in HEK cells overexpressing its close relative TRPC3 [7]. These data suggested that the non-selective Ca-conducting cation channel TRPC6 [4] could play a role in the mineral status of cells. Since the cloning of TRPC6 from murine brain tissue [9] many groups have provided significant insight into its expression and functions [1,10].…”
Section: Introductionmentioning
confidence: 91%
“…For instance, TRPC6 opens in response to the stimulation of some G-protein coupled receptors, after a direct application of diacylglycerol (or diacylglycerol analogues) [2], or in response to hyperforin [3], a bioactive molecule extracted from the medicinal herb Hypericum perforatum. Whatever the activation mode, the opening of TRPC6 channels triggers an influx of sodium (Na) and calcium (Ca) ions [4]. In addition, electrophysiological and imaging experiments conducted on HEK cells, the neuronal cell line PC12 and cortical neurons in primary cultures proposed that TRPC6 could also function as an uptake pathway for essential metals like iron (Fe) [5,6] and zinc (Zn) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…TRPC belongs to the superfamily of TRP cation channels that are non-selectively permeable to calcium [15,17]. Biophysical properties of TRPC6, including details about its permeation and rectification in renal and heterologous systems, have been recently discussed [18]. Briefly, TRPC channels can be activated by stimulating tyrosine phosphorylation-dependent cascade through phospholipase C (PLC).…”
Section: Trpc6 and Its Regulation By Gpcrmentioning
confidence: 99%